2024
DOI: 10.15277/bjd.2024.431
|View full text |Cite
|
Sign up to set email alerts
|

Participant experiences during the NHS Low Calorie Diet Programme pilot. Findings from an online survey

Duncan Radley,
Kevin Drew,
Catherine Homer
et al.

Abstract: Background: In 2020, NHS England commissioned independent commercial service providers to deliver a Low Calorie Diet Programme pilot, offering Total Diet Replacement alongside behavioural support. Methods: This paper presents participant experiences of the programme using both quantitative and qualitative data derived from four cross-sectional surveys, and examines differences by sociodemographics, delivery model and provider. Results: The majority of participants reported a positive experience with the referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The findings from the study, with recommendations for policy, practice and research, are presented elsewhere: total diet replacement phase; 23 food reintroduction phase; 24 weight maintenance phase; 25 interviews with individuals who withdrew; 27 and the participant experiences survey. 26 In addition there will be dissemination through a series of peer-reviewed publications, national and international conference presentations, alongside public facing blogs and vlogs on the Re:Mission study website, 33 accompanied by an illustrated journalstyle summary of the final report and a short film documenting service user journeys through the photovoice materials.…”
Section: Results and Disseminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from the study, with recommendations for policy, practice and research, are presented elsewhere: total diet replacement phase; 23 food reintroduction phase; 24 weight maintenance phase; 25 interviews with individuals who withdrew; 27 and the participant experiences survey. 26 In addition there will be dissemination through a series of peer-reviewed publications, national and international conference presentations, alongside public facing blogs and vlogs on the Re:Mission study website, 33 accompanied by an illustrated journalstyle summary of the final report and a short film documenting service user journeys through the photovoice materials.…”
Section: Results and Disseminationmentioning
confidence: 99%
“…22 Findings from the studies detailed within this paper are reported elsewhere in this issue. [23][24][25][26][27]…”
Section: The Nhs Lcd Programmementioning
confidence: 99%
See 1 more Smart Citation
“…The intention to use TDR in this way was also reported in the participant survey and previous clinical trials. 14,15 Whilst TDR product use is considered safe and effective in the short term, further research is needed to explore implications associated with longer-term use. The relationship with their coach was seen as important by participants and was affected by delivery approaches as well as continuity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six accompanying papers, the first describes the qualitative evaluation methods employed; 9 the second, 10 third 11 and fourth 12 focus respectively on the TDR, food reintroduction and weight maintenance phases of the intervention; the fifth describes the findings of structured interviews with people who did not complete the intervention; 13 and the sixth presents participant experiences of the programme using both quantitative and qualitative data derived from four crosssectional surveys, and examines differences by sociodemographic characteristics, delivery model and provider. 14 Valuable learnings from the qualitative findings have already supported, and will continue to support, improvements in the programme, to better meet the needs of participants, as well as referrers, providers and health systems. With full national coverage now almost complete, enabling potential universal access, people living with diabetes, healthcare professionals, commissioners and organisations such as ABCD, PCDS and Diabetes UK can work together to ensure that the option of the NHS Type 2 Diabetes Path to Remission Programme is embedded into, and aligned with, routine T2DM care pathways across England, from the point of diagnosis.…”
mentioning
confidence: 93%